2017
DOI: 10.5176/2251-1865_cbp17.14
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Bilingual Processing of Positive and Negative Information

Abstract: Abstract-Past research suggests that the emotional content of words has greater impact when presented in a bilingual's first language (L1) compared to their second language (L2). This is predicted to be a consequence of automatic processing of emotional words in L1 compared to slower, semantic processing in L2. In the current study 58 Chinese-English bilinguals from Hong Kong rated the valence and arousal of positive, neutral, and negative words presented in Chinese (L1) and English (L2). In contrast to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The exact reasons for these unexpected findings are unknown, so a potential explanation is proposed. Chinese-English (L1-L2) bilinguals from Hong Kong who rated the valence and arousal of positive, neutral, and negative words presented in both languages demonstrated both a more positive reaction to positive words and a more negative reaction to negative words in English than in Chinese; however, for the arousal rating, the negative words in Chinese were rated as having a greater arousal effect than were the negative words in English (Ong, Hussain, Chow, & Thompson, 2017). These results suggest that the valence and arousal ratings of bilinguals can be decoupled, at least with regard to negative words.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact reasons for these unexpected findings are unknown, so a potential explanation is proposed. Chinese-English (L1-L2) bilinguals from Hong Kong who rated the valence and arousal of positive, neutral, and negative words presented in both languages demonstrated both a more positive reaction to positive words and a more negative reaction to negative words in English than in Chinese; however, for the arousal rating, the negative words in Chinese were rated as having a greater arousal effect than were the negative words in English (Ong, Hussain, Chow, & Thompson, 2017). These results suggest that the valence and arousal ratings of bilinguals can be decoupled, at least with regard to negative words.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the valence and arousal ratings of bilinguals can be decoupled, at least with regard to negative words. Because the bilingual participants in the this study were living in a similar language environment than were the participants in the study conducted by Ong et al (2017), they potentially felt less arousal from negative words in English but remained sensitive to valence. In terms of arousal, a psychophysiological study indicated that negative high-arousal pictures elicited higher late positive potential (LPP) responses than did negative low-arousal pictures, and trait mindfulness was associated with decreased LPP responses elicited by negative high-arousal pictures but not by negative low-arousal pictures (Lin, Fisher, Roberts, & Moser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Emotion research in the bilingual literature, however, has shown that emotional content of language is also vulnerable to age affects, particularly when the second language is learnt through formal education (Caldwell-Harris, Sanches & Nayaka, 2014;Chen, Lin, Chen, Lu & Guo, 2015;Ong, Hussein, Chow & Thompson, 2017). However, it is maintained that proficiency level or length and amount of exposure may compensate for the age and context of acquisition effects (Grabitz, Watkins & Bishop, 2016;Kazanas & Altarriba, 2016;Ong, Hussain, Chow & Thompson, 2017).…”
Section: обробка слів-емоцій при пізньому вивченні L2mentioning
confidence: 99%
“…Studies conducted with healthy subjects (Dewaele, 2004a(Dewaele, , 2004bPavlenko, 2004;Kim & Starks, 2008) as well as those with theraupatic cases (Freud, 1893cited in Pavlenko, 2012 and psychophysiological studies support this view (Harris, 2004;Caldwell-Harris, Sanchez & Nayaka, 2014). However, it is maintained that proficiency (Ong, Hussain, Chow & Thompson, 2017) and frequency of use of the languages (Kazanas &Altarriba, 2016) may affect the extent of perceived emotionality in L2.…”
Section: обробка слів-емоцій при пізньому вивченні L2mentioning
confidence: 99%
“…Other studies revealed that the emotional content of words has a stronger effect when presented in a bilingual's first language (L1) in comparison with their second language (L2) (Ferré et al, 2010;Conrad et al, 2011;Opitz and Degner, 2012;Chen et al, 2015;Kazanas and Altarriba, 2016;Rosselli et al, 2017). This is most likely explained by automatic processing of emotional words in L1 compared to slower, semantic processing in L2 (Ong et al, 2017). However, one study on Chinese-English bilinguals indicated that emotional word processing might be affected by the proficiency and complexity of the respective language (Ong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%